The mapping of mRNA alterations elucidates the etiology of radiation-induced pulmonary fibrosis - Yuan, Meng; Zhao, Maoyuan; Sun, Xin; Hui, Zhouguang (Frontiers in Genetics, 2022)
The etiology of radiation-induced pulmonary fibrosis is not clearly understood yet, and effective interventions are still lacking. This study aimed to identify genes responsive to irradiation and compare the genome expression between the normal lung tissues and irradiated ones, using a radiation-induced pulmonary fibrosis mouse model. We also aimed to map the mRNA alterations as a predictive model and a potential mode of intervention for radiation-induced pulmonary fibrosis. Thirty C57BL/6 mice were exposed to a single dose of 16 Gy or 20 Gy thoracic irradiation, to establish a mouse model of radiation-induced pulmonary fibrosis. Lung tissues were harvested at 3 and 6 months after irradiation, for histological identification. Global gene expression in lung tissues was assessed by RNA sequencing. Differentially expressed genes were identified and subjected to functional and pathway enrichment analysis. Immune cell infiltration was evaluated using the CIBERSORT software. Three months after irradiation, 317 mRNAs were upregulated and 254 mRNAs were downregulated significantly in the low-dose irradiation (16 Gy) group. In total, 203 mRNAs were upregulated and 149 were downregulated significantly in the high-dose irradiation (20 Gy) group. Six months after radiation, 651 mRNAs were upregulated and 131 were downregulated significantly in the low-dose irradiation group. A total of 106 mRNAs were upregulated and 4 downregulated significantly in the high-dose irradiation group. Several functions and pathways, including angiogenesis, epithelial cell proliferation, extracellular matrix, complement and coagulation cascades, cellular senescence, myeloid leukocyte activation, regulation of lymphocyte activation, mononuclear cell proliferation, immunoglobulin binding, and the TNF, NOD-like receptor, and HIF-1 signaling pathways were significantly enriched in the irradiation groups, based on the differentially expressed genes. Irradiation-responsive genes were identified. The differentially expressed genes were mainly associated with cellular metabolism, epithelial cell proliferation, cell injury, and immune cell activation and regulation.